661 EFFICACY OF ROBOT ASSISTED MINIMALLY INVASIVE ESOPHAGECTOMY: PROPENSITY MATCHED ANALYSIS OF RAMIE IN COMPARISON WITH CONVENTIONAL MIE. (17th September 2021) - Fujita, Takeo; Sato, Kazuma; Ozaki, Asako; Akutsu, Tomohiro; Fujiwara, Hisashi; Daiko, Hiroyuki
Abstract:  : Robot assisted minimally invasive esophagectomy (RAMIE) has been reported to be potential advantages in previous reports. Here we demonstrate the difference between these two minimally invasive procedures and investigated the surgical results of RAMIE in comparison with MIE using propensity matched-cohort. Methods: We investigated 154 cases of thoracic esophagectomy conducted between 2020/1 to 2021/1. Among these cases, we analyzed 30 cases of RAMIE in comparison with 30 cases of matched-cohort which conducted conventional thoracoscopic esophagectomy (MIE) in the prone. Then we evaluated the surgical results between two groups. Results: There were no differences in age (69.2 vs 69.1 yo), gender (M:F = 24:6 vs 24:6), cStage (Stage I, II, III, IV:6, 3, 14, 7 vs 8, 3, 14, 5), and preoperative chemotherapy (70% vs 66.7%) between RAMIE and matched-cohort MIE. There was statistically significant difference in total time of thoracic phase (233.1 vs 173.3 min; p < 0.01). There were no significant differences in postoperative events in RAMIE vs MIE (Clavien-Dindo Grade 1≧; Recurrent laryngeal nerve paralysis (RLNP) (16.7 vs 20.0%; p = 0.19). However, after the learning curve archived, seldom cases were diagnosed postoperative RLNP in RAMIE cases in comparison with MIE (p = 0.06). Conclusion: We demonstrated the formalization of our procedure and surgical results of RAMIE. There were no significant differences in postoperative events between two groups. However RLNP was lower after the learning peak. Incidence of RLNP could be reduced in RAMIE.